THE RELATIONSHIP BETWEEN PERSONAL HYGIENE BEHAVIOR AND THE INCIDENCE OF SCABIES AT THE TAHFIDZ QUR'AN YAPILA ISLAMIC BOARDING SCHOOL IN LANGSA CITY - Nurul Maulidya; Ajmain Ajmain; Nurhayati Ningsih; Deviana Risa (Universitas Bina Bangsa Getsempena, 2025)
Scabies is still a problem in developing countries. In addition to poor personal hygiene behavior among students which can increase the risk of contracting scabies. The aim of this research is to determine the relationship between personal hygiene behavior and the incidence of scabies at the Tahfidz Qur'an Islamic Boarding School, Yapila Langsa. Method: Analytical research method with cross sectional design. The population in this study was all students at the Tahfidz Qur'an Islamic Boarding School Yapila Langsa, totaling 200 students, the sampling technique was carried out using Total Sampling. The results of the research show that of the 200 respondents the majority did not experience scabies, 124 respondents (62%), the majority of respondents had good personal hygiene, 160 respondents (80%) and the majority of respondents who implemented good personal hygiene did not experience scabies, 121 respondents. (75.6%) while the majority of respondents who practiced poor personal hygiene experienced scabies as many as 37 respondents (92.5%). There is a relationship between personal hygiene and the incidence of scabies with a p-value of 0.002 (p<0.05). Researchers suggest to the Tahfidz Qur'an Yapila Langsa Islamic Boarding School to improve and increase the quality of education and focus on clean and healthy living behavior.